Pelatihan Ketrampilan Pembuatan Mahar : Upaya untuk Meningkatkan Kreatifitas dan Kemandirian Ekonomi di Wilayah PKK RW 15 Kel. Meteseh Kota Semarang - Asah Wiari Sidiq; Ahmad Sahri Romadon; Citra Rizkiana; Rahma Prafinta Sari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The problem faced by partners in community service activities is the low level of creative economic skills among housewives in RW 15, Meteseh Village, Semarang City. This condition has an impact on limited family economic independence, so efforts are needed to develop entrepreneurial potential that is in line with community needs. One potential business opportunity is making wedding dowries, given the stable and growing market demand. However, limited knowledge, creativity, and skills in producing attractive dowry products with sales value are the main obstacles faced by partners. This community service program aims to increase the creativity and economic independence of housewives through dowry making skills training. The method used includes a phased training, starting from an introduction to materials and basic dowry making techniques, developing creative designs, and product marketing strategies both digitally through social media and directly (offline). Participants are also provided with mentoring to improve their understanding of simple business management, product branding, and promotional techniques to be competitive in the market. The target outputs of this activity include the creation of an independent dowry making business, the production of quality dowry products with creative designs, and improving participants' ability to market their products. In addition, this activity resulted in video documentation of the implementation, potential registration of Intellectual Property Rights (IPR), and publication in a community service journal. The evaluation results showed a significant increase in participants' knowledge and skills based on a comparison of pre-test and post-test results. Before the training, most participants did not understand basic techniques or product marketing strategies.